Preferencyjne porozumienia handlowe Chińskiej Republiki Ludowej - Mazur, Grzegorz (Preferential trade agreements of the People’s Republic of China, 2009)
Incorporation of China into the international trade and economic system was initially based on multilateral initiatives and arrangements for WTO membership. Since the end of the 90s this country, similarly to the whole region of East Asia, expressed more interest and willingness to co-operation based on bilateral and regional agreements. In accordance with ‘bilateral strategy’ that was launched actively after obtaining the membership in WTO several preferential trade and economic agreements were concluded with both Asian countries (ASEAN, Hong Kong, Macao, Singapore, Pakistan) and states from other regions (Chile, New Zealand). During the last few years bilateral strategy of Chinese trade policy has become a parallel and an alternative platform to multilateralism and enabled China to defend and realize more selectively its economic interests. Ongoing negotiations on future free trade agreements with many new countries will facilitate and stimulate further economic and trade cooperation. However, it should be borne in mind that these actions weaken other initiatives and obstruct the successful conclusion of multilateral trade rules on WTO forum. Moreover, too many preferential trade agreements (defined as “the spaghetti bowl” syndrome), additionally restricted only for new members, may hamper co-operation and economic integration in the region, in this case in East Asia
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 40-50